Pathology of Fowl Typhoid and Molecular Detection of its Pathogen (Annals of Bangladesh Agriculture, 2019)
Salmonellae are important group of pathogens responsible for human and animal diseases. The present study was undertaken with the aim to study pathology of fowl typhoid caused by Salmonella entarica subsp. enteric serovar Gallinarum and to identify Salmonella serovars by polymerase chain reaction (PCR) based molecular method isolated from commercial layer, broiler and sonali chickens of Gazipur district, Bangladesh. A total of 150 cloacal, intestinal and liver swab samples were collected in sterie nutrient and tetrathionate broth from apparently healthy, sick and dead chicken the necropsy. Organ samples were collected in 10% buffered neutral formalin. The collected tissues were fixed, processed, sectioned, stained with hematoxylin and eosin (H&E) and examined at low and high power microscopic fields. Grossly, the liver appeared larger and hemorrhagic with focal necrosis. Catarrhal inflammation on intestinal mucosa was seen. The ova were deformed, discolored and cystic. Microscopically, focal necroses with the infiltration of mononuclear cells were seen with congestion of the central vein. Spleen showed severe depletion of lymphoid cells in white pulp along with reticuloendothelial cell hyperplasia. The section of ovary showed deformed ova with hemorrhages. Samples were subjected to various cultural, biochemical, and molecular examinations and the prevalence was identified 28% cases. Isolated bacteria appeared gram (-)ve, and arranged in short chain. PCR was performed targeting invA gene of Salmonella Gallinarum and amplified 184-bp fragment of the isolates confirmed specific infectivity.Ann. Bangladesh Agric. (2019) 23(2) : 49-60